PENGARUH LIKUIDITAS DAN LEVERAGE TERHADAP KEMANDIRIAN DAERAH (STUDI TERHADAP LAPORAN KEUANGAN PEMERINTAH DAERAH TAHUN ANGGARAN 2007 DI WILAYAH PROVINSI ACEH) - Waskito Hadi (Program Magister Akuntansi Unsyiah, 2010)
The research was conducted using secondary data of LKPD TA 2007 in Aceh Province which was proposed to understand the influence of liquidity and leverage towards regional autonomy using path analysis with census data partially and simultaneously.The population of this research are audited financial statements of local government in Aceh (LKPD) for the budget year of 2007 by Supreme Audit Board of Indonesia (BPK- RI) Representatives Office in Aceh Province. The audit reports had been published widely through the official site of BPK- RI. The final population of this research were 14 financial statements of local government in Aceh. Using SPSS version 12, the result showed that the influence of liquidity towards regional autonomy was strong with the percentage 74,3%; whereas the percentage of leverage influence towards regional autonomy was 2,2 %. Simultaneous influence of liquidity and leverage towards regional autonomy was showed with determination coefficient value of 0,520. Finally, the percentage of influence of other variables towards regional autonomy (e) was 0,480.Based on the results, it can be concluded that liquidity and leverage have influence towards regional autonomy either simultaneously or partially. Key words: liquidity, leverage and regional autonomy.